Nouveaux territoires et nouvelles identités culturelles : revue des études sur la diaspora chinoise a l’ère d’Internet - Joy Raynaud (Netcom)
For over a thousand years, the Chinese Diaspora has been mainly based on structured networks supporting the individual and collective success socially (integration), economically (financial success) and culturally (preservation of Chinese cultural identity). But what happens to these social networks in the era of globalization, with the massive use of technical and technological networks? From a literature review, this work provides a synthesis of similarities in the Chinese Diaspora communities with Internet usage. Several studies seek to demonstrate that ICTs provide new Chinese immigrants the opportunity to redefine their cultural identities hybrid and fragmented between breaks and continuities of tradition. It is shown that Internet disrupts the concepts of distance and territory as an essential tool for adaptation of immigrants in host countries while excluding the need for spatial proximity. Moreover, its use generates, among Chinese immigrants, the feeling of "being present" in the country of origin, but nevertheless located several thousands of kilometers away.